2015
DOI: 10.1007/s10620-015-3919-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Rebleeding in Peptic Ulcer Bleeding: A Second Look at Second-Look Endoscopy

Abstract: Rebleeding, which occurs in 10-15 % of patients with peptic ulcer bleeding (PUB) [1], is associated with a twoto fivefold mortality increase, depending on the presence of other risk factors [2]. Therefore, identification of the predictors of rebleeding seems meaningful in order to identify high-risk patients needing close observation and rapid treatment in case of the development of rebleeding.According to previous studies, hemodynamic shock, usually defined as a systolic blood pressure \100 mmHg, often combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…27 The results of this study showed that there will be no difference in the final outcome of the patient with a second endoscopy, this finding is consistent with a number of previous studies. 28 In the mentioned studies, initial endoscopy alone with full endoscopic hemostasis in reducing the risk of rebleeding, mortality or the need for surgery in patients with acute upper gastrointestinal bleeding is not different compared with the second endoscopy and even causes fewer complications to the patient. 27 According to a study, second-time endoscopy with thermal treatment reduces the risk of rebleeding, but has no effect on overall mortality or the need for surgery.…”
Section: Discussionmentioning
confidence: 98%
“…27 The results of this study showed that there will be no difference in the final outcome of the patient with a second endoscopy, this finding is consistent with a number of previous studies. 28 In the mentioned studies, initial endoscopy alone with full endoscopic hemostasis in reducing the risk of rebleeding, mortality or the need for surgery in patients with acute upper gastrointestinal bleeding is not different compared with the second endoscopy and even causes fewer complications to the patient. 27 According to a study, second-time endoscopy with thermal treatment reduces the risk of rebleeding, but has no effect on overall mortality or the need for surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In the selection of treatment methods, ulcer size was considered a criterion in accordance with the current guidelines. [8] Endoclips were placed at the ulcer sites in all patients. In patients with active bleeding despite the application of endoclips, 0 to 2 mg epinephrine was injected if the ulcer size was less than 2 cm, while 2 to 4 mg epinephrine was injected if the ulcer size was larger than or equal to 2 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopy was performed with single-channel endoscopes (EPX-3500 HD, Fujifilm, Singapore; EPK-i5000, Pentax, Japan) by endoscopists with 5 years of experience treating patients with PUB. In the selection of treatment methods, ulcer size was considered a criterion in accordance with the current guidelines [8] . Endoclips were placed at the ulcer sites in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study from our group using patients with artificial ulcers that formed after gastric endoscopic submucosal dissection (ESD), second-look endoscopy was not necessary [8]. Although the situation between artificial ulcers and PUs might be different, there is another concern of cost-effectiveness even in the case of PUs, since performance of SLE was only cost-effective after therapeutic endoscopy if the risk of re-bleeding was [31 % according to one study [9]. Furthermore, our study revealed that SLE group showed a higher re-bleeding rate than non-SLE group (5.4 vs. 3.8 %) [8].…”
mentioning
confidence: 99%